Cauda equina syndrome post epidural steroid injection - Ang, Poh Thean; Zakaria@Mohamad, Zamzuri; Karupiah, Rajandra Kumar; Awang, Mohd Shukrimi (Juniper Publishers, 2018)
We report a case of a 62-year-old lady who developed cauda equina syndrome post- epidural steroid injection. She undergone an epidural injection to relieve her radiculopathy pain caused by underlying lumbar spinal canal stenosis L4/L5 and L5/S1. Post epidural injection she developed an acute bowel and bladder dysfunction, worsening pain and weakness over her bilateral lower limbs with saddle anesthesia which did not resolve after 6 days. Her repeated magnetic resonance imaging (MRI) post- epidural injection shows no evidence of extradural hemorrhage/ collection and is unremarkable as compared to her pre- epidural magnetic resonance images. She undergone emergency laminectomy of L4/ L5 and L5/S1. Post laminectomy, her bilateral lower limb pain resolved, power restored, and she regained her bowel and bladder functions. The development of cauda equina syndrome post epidural injection have been reported as a rare complication and is commonly associated with local anesthetic toxicity, direct trauma of the needle to the spinal cord or the development epidural hematoma post injection. However, in this case there was no evidence of epidural hematoma both on magnetic resonance imaging and intraoperatively. Complete neurological recovery occurs following laminectomy suggesting the likely cause of cauda equina syndrome in this case is more to a mechanical compression.